2005
DOI: 10.1097/00004850-200503000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of response to risperidone treatment with respect to plasma concencentrations of risperidone, catecholamine metabolites, and polymorphism of cytochrome P450 2D6

Abstract: In the present study, we examined the relationships between plasma concentrations of risperidone and clinical responses, extrapyramidal symptoms, plasma levels of cotinine and caffeine, or cytochrome (cyp)2D6 genotypes. In addition, we also investigated the relationships between plasma levels of 3-methoxy-4-hydroxyphenylglycol (MHPG) or homovanillic (HVA) acid and clinical responses to risperidone. One hundred and 36 patients (male/female: 58/78, age 37+/-13 years) who met DSM-IV criteria for schizophrenia, sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 26 publications
4
51
0
Order By: Relevance
“…In recent studies, it was observed that CYP2D6 did not predict response to risperidone, but predicted metabolic ratios and side effects. [62][63][64] No association was found between CYP2D6 PM variants and clozapine response. 65 However, small adjustments of therapeutic doses of clozapine are recommended according to CYP2D6 genotypes, suggesting that these enzymes are only minor pathways for clozapine metabolism.…”
Section: Pharmacokinetic Factorsmentioning
confidence: 98%
“…In recent studies, it was observed that CYP2D6 did not predict response to risperidone, but predicted metabolic ratios and side effects. [62][63][64] No association was found between CYP2D6 PM variants and clozapine response. 65 However, small adjustments of therapeutic doses of clozapine are recommended according to CYP2D6 genotypes, suggesting that these enzymes are only minor pathways for clozapine metabolism.…”
Section: Pharmacokinetic Factorsmentioning
confidence: 98%
“…Nine studies 58,60,70,76,78,88,89,96,97 clearly specified the number of missing genotypes and six of these provided reasons for the missing data. 58,60,70,76,78,96 In the remaining 42/51 studies, it was unclear whether the number contributing to each analysis was equal to the sample size.…”
Section: Clinical Validitymentioning
confidence: 99%
“…Ten studies were interested in the relationship between efficacy and CYP2D6 [90][91][92][93][95][96][97][98][99] or CYP1A2. 94 A wide variety of outcomes were considered across the studies but no two studies measured outcomes in exactly the same way.…”
Section: Clinical Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…First, the sample size (n ¼ 270), though limited, was higher than the mean sample size used in pharmacogenetic studies of acute AP-induced EPS (n ¼ 150). [7][8][9][10]32,33,[35][36][37][38][39][40][41][42][43][44][45] In fact, to our knowledge, only one study of Caucasians had a larger sample (n ¼ 665). 36 Second, although Bonferroni correction seems the most appropriate way to correct for multiple testing, it may be overly conservative.…”
Section: Discussionmentioning
confidence: 92%